2019
DOI: 10.1038/s41366-019-0402-4
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 deficiency exacerbates lipopolysaccharide-induced inflammation in adipose tissue

Abstract: Background/objectives Pentraxin 3 (PTX3) has been characterized as a soluble and multifunctional pattern recognition protein in the regulation of innate immune response. However, little is known about its role in adipose tissue inflammation and obesity. Herein, we investigated the role of PTX3 in the regulation of lipopolysaccharide (LPS)-induced inflammation in adipocytes and adipose tissue, as well as high-fat diet (HFD)-induced metabolic inflammation in obesity. Methods Ptx3 knockdown 3T3-L1 Cells were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
6
11
0
Order By: Relevance
“…Thus, we detected that pentraxin-3 protein is seven times elevated in MSCs vesicles compared to those from the same cells after differentiation. This protein has a protective role in LPS and high fat diet-induced inflammation in murine adipose tissue [55], thus, it may suggest a functional anti-inflammatory role of those vesicles secreted by MSCs as previously described [56].…”
Section: Despite the Recent Up Surge Of Extracellular Vesicles Revealsupporting
confidence: 61%
“…Thus, we detected that pentraxin-3 protein is seven times elevated in MSCs vesicles compared to those from the same cells after differentiation. This protein has a protective role in LPS and high fat diet-induced inflammation in murine adipose tissue [55], thus, it may suggest a functional anti-inflammatory role of those vesicles secreted by MSCs as previously described [56].…”
Section: Despite the Recent Up Surge Of Extracellular Vesicles Revealsupporting
confidence: 61%
“…Although eWAT expressed the highest levels of PTX3 among three fat depots, the expression levels of miR‐21 and miR‐146 were very low and not regulated by PTX3 deficiency in eWAT in male mice. Interestingly, our previous studies in female mice showed that BAT and iWAT expressed higher levels of PTX3 than eWAT . Taken together, our results suggest that PTX3, which displays a sex and depot difference in its expression, regulates inflammation possibly through a different mechanism in different adipose depots as well as between the sexes.…”
Section: Discussionsupporting
confidence: 57%
“…However, the role of PTX3 in adipocyte inflammation and how PTX3 regulates the inflammatory process in adipocytes are not fully understood. Our previous study showed that knocking down PTX3 exacerbated lipopolysaccharide (LPS)–induced inflammation in adipocytes, and the peak of LPS‐induced PTX3 expression in adipose tissue appeared later than that of the expression of inflammatory cytokines and the activation of nuclear factor (NF)‐κB. These results suggest that PTX3 functions in resolving inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…PTX3 also plays a role in synaptogenesis in the developing brain ( Fossati et al, 2019 ). Furthermore, PTX3 deficiency results in augmented infarct area following myocardial ischemia/reperfusion injury ( Salio et al, 2008 ), increased macrophage accumulation and inflammation in atherosclerotic plaques ( Norata et al, 2009 ), and exacerbated proinflammatory gene expression in visceral adipose tissue from a high fat diet-induced obese mice ( Guo et al, 2020 ). Overall, PTX3 can mediate multiple beneficial effects in various disease states through antiinflammatory and neuroprotective actions.…”
Section: Discussionmentioning
confidence: 99%